CEPEJ Gudelines for Mediation Resolving Administrative Disputes – A Comparison between Council of Europe States and Ukrainian Perspectives - Serhieieva, Alina (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The status of Ukraine as a candidate country for the European Union membership reinforces the need for comparative analysis between Ukrainian regulations and law of other EU Member States as well as European regulations. One of the fields of comparative law is a development of mediation for disputes covered by administrative law. It has already been a subject of interest and promotion to both – The EU and the Council of Europe, since European standards of democracy provide for state cooperate with citizens/individuals. The aim of this article is, to examine the main provisions, recommendations and best practices of the CoE member states, and to analyse the current practice and existing gaps in Ukraine in order to develop a proposal for effective implementation in the light of the most recent CEPEJ Guidelines promoting mediation to resolve administrative disputes. A comparative overview of this type of mediation regulations may be considered as novum. As for methodology, the paper is dominated by the logical-linguistic and comparative method. So far – though Ukrainian legal system is quite compatibile with the examined CEPEJ gudelines and provide for inter-branch solutions – the development of administrative and court-administrative mediation is quite resilient and there is still much to be done not solely with legal regulations, but also „mediation culture” in such field.